2011
DOI: 10.3168/jds.2010-3580
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of monensin with dietary fat and carbohydrate components on ruminal fermentation and production responses by dairy cows

Abstract: Variation in milk fat percentage resulting from monensin supplementation to lactating dairy cows could be due to altered ruminal fermentation with interactions of monensin with ruminal biohydrogenation of fat and ruminal carbohydrate availability. The objective of the study was to determine the effects of feeding monensin as Rumensin (R) in diets differing in starch availability (ground or steam-flaked corn), effective fiber (long or short alfalfa hay, LAH or SAH), and 4% fat (F) from distillers grains, roaste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 55 publications
3
45
1
Order By: Relevance
“…With the exception of isobutyrate and isovalerate molar proportions which were higher (P < 0.01) for cows fed MON compared with cows fed CTL, the molar proportions of the other VFA and the acetate : propionate were unaffected by dietary addition of MON. Previous (Benchaar et al, 2006) and recent (Mathew et al, 2011) studies also observed no change in the acetate : propionate ratio in dairy cows supplemented with MON. In contrast, Sauer et al (1998) reported that feeding MON decreased the acetate : propionate ratio in dairy cows.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…With the exception of isobutyrate and isovalerate molar proportions which were higher (P < 0.01) for cows fed MON compared with cows fed CTL, the molar proportions of the other VFA and the acetate : propionate were unaffected by dietary addition of MON. Previous (Benchaar et al, 2006) and recent (Mathew et al, 2011) studies also observed no change in the acetate : propionate ratio in dairy cows supplemented with MON. In contrast, Sauer et al (1998) reported that feeding MON decreased the acetate : propionate ratio in dairy cows.…”
Section: Resultsmentioning
confidence: 89%
“…In agreement with our findings, Grainger et al (2010) also reported no change in DMI of cows fed MON at a feeding rate similar to that used in our study. Likewise, Mathew et al (2011) observed no effect of MON on nutrient digestibility in dairy cows. In contrast, Benchaar et al (2006) reported increased CP digestibility in cows supplemented with MON.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Another study has reported that the supplementation of lactating Holstein cows with monensin decreased VFA (5). Furthermore, Mathew et al (23) have reported that the supplementation of cows with monensin and tallow together results in a decrease in total VFA. In contrast with the current study, Lewis et al (21) have reported that cows fed tallow did not have a significant change in total VFA production compared to controls, but they did have a significant increase in propionic acid content as well as decreases in acetic acid content and the acetate:propionate ratio.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism through which lipid could specifically enhance monensin is not clear. Clary et al (1993) and Mathew et al (2011), who tested effects of dietary lipid on monensin, did not find any significant change in acetic to propionic ratios or protozoan numbers in the rumen in response to addition of lipid over monensin. However, drawing a sensible conclusion about the interaction between dietary lipid and monensin is difficult because half of the dairy cow studies were based on fresh forages (Table 1) and about half of the forage EE comprises undegradable cuticular waxes.…”
Section: Effects Of Monensin and Explanatory Variables From Mixed Effmentioning
confidence: 99%